Pengaruh Gaya Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Karyawan pada UPTD Jalan dan Jembatan Wilayah Pelayanan 1 - Haryani, Putri; Siska, Elmira (Lembaga Pengembangan Kinerja Dosen, 2024)
Leadership style and work discipline play an important role in improving employee performance. This study aims to examine the influence of leadership style and work discipline on employee performance at UPTD roads and bridges in the service area of ​​1 SPPJJ unit in Depok City, Bogor City and Bogor Regency 1. The population in this study is all SPPJJ employees in Depok City, Bogor City and Bogor Regency. 1 as many as 31 people. By using quantitative methods and collecting data using questionnaires. Data analysis uses data quality tests, namely validity tests and reliability tests, and classical assumption test analysis, namely: normality test, heteroscedasticity test, multicollinearity test, linearity test, hypothesis testing and coefficient of determination. The research results show that simultaneously leadership style and work discipline have a significant effect on employee performance. The coefficient of determination value is 0.341 which explains that the influence of leadership style and work discipline on employee performance variables is 34.1%. It is hoped that the results of this research will lead leaders in the UPTD roads and bridges service area 1 of the SPPJJ unit of Depok City, Bogor City and Bogor Regency 1 to develop a leadership style and continue to improve their work discipline to obtain maximum performance.